Bermain Sambil Belajar: Permainan Tradisional Sebagai Media Penanaman Nilai Pendidikan Karakter - Arif Syamsurrijal (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2020)
Abstract The world of children is a world of play. So, using games for the learning process is the right thing to do. There are quite a number of games to choose from, but traditional games have their own uniqueness, especially Indonesia which has quite a lot of traditional games. The game is an ancestral heritage that contains many moral values. Besides being fun, this game is also a medium for internalizing noble values that should be preserved. This short article is a descriptive article that explains how the games that are now starting to be abandoned by today's children have a lot of things that we need to keep and take care of.